Reconfiguring Muhammadiyah’s Intellectual-Political Thought in Strengthening Civil Society from the Jokowi Era to the Prabowo–Gibran Era - Yudaningsih Yudaningsih (Jurnal Iman dan Spiritualitas, 2026)
The relationship between religion and state in Indonesia since the Reformation era has been characterized by complex dynamics, with religious organizations playing a crucial role in balancing state power and civil society interests. In this context, Muhammadiyah has long served as a key actor in Islamic civil society, serving both as a counterbalancing force to the state and as a driver of social transformation. This study examines the transformation of Muhammadiyah's intellectual-political thinking in response to shifting power configurations and democratic dynamics during the Joko Widodo administration and the transition to the Prabowo Subianto–Gibran Rakabuming Raka administration. Using a qualitative approach based on desk research and limited interviews, the study finds that Muhammadiyah's political thinking has evolved into a more strategic and adaptive orientation. This transformation reflects Muhammadiyah's efforts to reinterpret its political role through social da'wah (Islamic outreach) and national responsibility while maintaining its identity as a progressive Islamic movement. It also strengthens civil society through critical, participatory, and collaborative engagement in public policy, social services, and humanitarian diplomacy. Overall, Muhammadiyah offers a constructive model of religion-state relations that combines organizational independence, public participation, and a commitment to democratic values ​​and social justice.